Tumor infiltrating lymphocytes in malignant melanoma - allies or foes? - Zidlik, Vladimir; Bezdekova, Michala; Brychtova, Svetlana (Biomedical papers, 2020)
This is an overview of current problematics regarding the role of tumor infiltrating lymphocytes (TILs) in malignant melanomas. Various and often conflicting data have been published, correlating tumor type, stage, prognosis, as well as sex and age of patients. This is partly due to heterogeneity in scaling systems and unstandardized TILs grading but also due to changes of tumor-host interactions. Melanomas are an immunologically heterogeneous group with variability of TILs, where distinct gene expression patterns were found in tumors with absent, and/or non- brisk TIL grade versus brisk TIL grade. However, the presence of TILs alone appears to be inadequate for implicating them as immunologically functional. Further characterisation of TIL phenotype and function is warranted. This especially concerns, evaluation of TILs of the suppressor phenotype but rather than as a prognostic factor, more for prediction of targeted immunotherapy.
Keywords: melanoma; tumor infiltrating lymphocytes; regulatory lymphocytes; immune check point